Iot based Parking Sensor Network for Smart Campus - Singh, Joseph Jesawanth; Ravi, Nanthiine Nair; Krishnan, Prajindra Sankar (International Journal of Engineering and Technology, 2018)
The difficulty in finding parking spaces is growing into a more serious problem especially in urban areas. As the number of vehicles on the road continues to increase substantially, the difficulty in finding parking spaces increases even more. To combat this rising issue many cities have adopted a more organised and intelligent parking system which is also commonly known as smart parking system. This is to improve the efficiency of locating a parking spot, especially in an urban area. The smart parking system will often have sensors at parking spaces to determine the occupancy of the respective parking space. This occupancy value is relayed to a server by some specific communication protocol. The parking occupancy can then be displayed to the public by a Graphical User Interface (GUI) design which gets the occupancy values from a server. This project simulates the parking sensor network design in a smart campus setting by implementing the concept of the Internet of Things (IoT). This project uses ultrasonic sensors that are connected to a NodeMCU microcontroller to send the parking occupancy values to an online database implemented using Google Firebase. A mobile application with a GUI (Graphical User Interface) is also created using MIT App Inventor 2 to display the vacancy of parking by communicating with the online database. The results obtained in this project were promising. The successful implementation of this idea will allow users to save more time and money, not to mention that it can also help reduce carbon emissions from vehicles resulting in a more sustainable environment.